Hubungan Pengunaan Smartphone dengan Kejadian Computer Vision Syndrome (CVS) pada Mahasiswa Fakultas Kedokteran Universitas Kristen Krida Wacana Angkatan 2016 - William William; Flora Rumiati; Isalin Silvanny Homer (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
A smartphone is generally defined as a multifunctional cell phone that adds some functions of a personal digital assistant (PDA) to a cell phone or a camera phone. The American Optometric Association defines computer vision syndrome (CVS) as an eye problem with vision that starts with prolonged use of computers, electronic readers and mobile phones. The most common symptoms associated with CVS are eye strain, headaches, blurred vision, dry eyes, and pain. This study aims to analyze the relationship of smartphone use with the occurrence of computer vision syndrome in the students of the Faculty of Medicine at the Krida Wacana Christian University Class of 2016. This study was a cross sectional design with 75 respondents. The technique of collecting data and identifying CVS occurrences uses a questionnaire. Power obtained was analyzed using the chi square test. The results of this study indicate that the prevalence of CVS is 98.7% and there is no correlation between the duration of smartphone use and the CVS incidence (p 0.0404> 0.05). This shows that the relationship between the duration of smartphone use has no effect on the incidence of CVS in Krida Wacana Christian University Class of 2016 Medical Faculty students.